2008
DOI: 10.1021/op800181e
|View full text |Cite
|
Sign up to set email alerts
|

A Large Scale Process for the Preparation of Thymitaq

Abstract: The large scale manufacturing of the anticancer agent 2-amino-6-methyl-5-(pyridin-4-ylsulfanyl)-3H-quinazolin-4-one dihydrochloride (thymitaq) from 6-bromo-5-methylanthranilic acid is described. The chemical route consists of two chemical steps: formation of a bromoquinazolinone and a copper-mediated Ullman-like coupling between 4-mercaptopyridine and the bromoquinazolinone. During process development, sodium hydride was replaced with sodium hydroxide and a method for removal of copper, based on 2,4,6-trimerca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…This method has been employed successfully for the synthesis of promazine drugs like chlorpromazine, triflupromazine and acepromazine in good yield. Wennerberg et al [190] prepared the anticancer agent thymatiq in large scale by copper-mediated coupling between halide and 4-mercaptopyridine (Scheme 62b). Bagley et al reported a copper mediated methodology for the synthesis of P38α MAPK Clinical Candidate VX-745 by C-S coupling reaction (Scheme 62c) [191].…”
Section: C-s Cross-coupling Reactionsmentioning
confidence: 99%
“…This method has been employed successfully for the synthesis of promazine drugs like chlorpromazine, triflupromazine and acepromazine in good yield. Wennerberg et al [190] prepared the anticancer agent thymatiq in large scale by copper-mediated coupling between halide and 4-mercaptopyridine (Scheme 62b). Bagley et al reported a copper mediated methodology for the synthesis of P38α MAPK Clinical Candidate VX-745 by C-S coupling reaction (Scheme 62c) [191].…”
Section: C-s Cross-coupling Reactionsmentioning
confidence: 99%
“…Quinazolin-4(3H)-ones are important class of naturally occurring nitrogen heterocycles [1] among them 2-amino functionalized quinazolin-4(3H)-ones were extensively studied in medicinal chemistry for a variety of pharmacological properties, which include anti-cancer, [2,3,4] anti-hypertensive, [5] anti-hepatitis C, [6] anti-viral, [7] anti-hyperglycemic, [8] anti-malarial, [9,10] antiinflammatory, [11] anti-microbial [12] and anti-bacterial activity. [13] Some of the important bioactive molecules, with 2-amino quinazolin-4(3H)-one pharmacophore, are shown in (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Quinazolinones are one of the important nitrogen-containing heterocyclic motifs; it is found in more than 200 natural products as well as in several drugs (Figure ). , The quinazolinone derivatives possess a wide range of pharmacological activities such as antimalarial, anticancer, antimicrobial, antidiabetic, anti-inflammatory, antihypertensive, anticonvulsant, diuretic, among others. The synthesis of various natural and synthetic derivatives of quinazolinones has acquired immense attention by the scientific community because of their wide range of biological properties. …”
Section: Introductionmentioning
confidence: 99%